The Role of Low Dosage Combined Oral Contraceptive Pill in Perimenopausal Women - A. Abadi; Fatimah Usman; Awan Nurtjahyo; Cindy Kesty (RSUP Dr Moh Hoesin Palembang, 2021)
The perimenopausal period refers to the time period of the menstrual cycle and endocrine changes. Usually, it starts with a variation in the menstrual cycle length and ending with FMP. The rates of unwanted pregnancies for these women are reported to be around 40–45%. Thus, contraceptive counselling and contraceptive use among perimenopausal women are important aspects of their overall health care if they are sexually active and do not wish to become pregnant. One of them is by using low dose combined oral contraceptive pill containing ethynylestradiol (EE) containing less than 50 µg EE/day. It acts by supressing gonadotropin. There are several positive effects of COC, namely pregnancy prevention; regulation of menstrual cycle; relieving menopausal symptoms; bone protection; protection against ovarian, endometrial and colorectal cancer; lipid metabolism; and blood pressure lowering effect. In contrast, the negative effects of COC are increases the risk of breast cancer, venous thromboembolism, and myocardial infarction. We presented a literature review to describe the usage of low dosage combined oral contraceptive pill as one of contraception method in perimenopausal women, including its positive and negative effects.